Contemporary Oral Oncology : Diagnosis and Management - Kuriakose, Moni Abraham (Springer International Publishing : Imprint: Springer, 2017)
This is the second of four volumes that together offer an authoritative, in-depth reference guide covering all aspects of the management of oral cancer from a multidisciplinary perspective and on the basis of a strong scientific foundation. This volume addresses a range of management issues in oral cancer, from imaging and staging through to the roles of radiation therapy and chemotherapy. Principles of ablative surgery are explained, and neck dissection and sentinel lymph node biopsy techniques, described. Detailed consideration is also given to the management of complications, salvage surgery and re-radiation, the biologic basis of treatment failure, and emerging approaches to overcome treatment resistance. The inclusion of resource-stratified guidelines will meet the needs of practitioners in different geographic regions with varying resources.- Resumé vydavatel
Keywords: ústní dutina; maligní nádorová onemocnění; nádory; histopatologie; klinická epidemiologie; nádorová prevence; oral cavity; cancer; tumors; histopathology; clinical epidemiology; cancer prevention; elektronické knihy; kolektivní monografie; electronic books; collective monographs